2005
DOI: 10.2460/ajvr.2005.66.1999
|View full text |Cite
|
Sign up to set email alerts
|

Validation of magnetic resonance imaging for measurement of equine articular cartilage and subchondral bone thickness

Abstract: Magnetic resonance imaging provides a good representation of cartilage and subchondral bone thickness, supporting its use in the study and clinical diagnosis of osteochondral structure and alteration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
88
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(94 citation statements)
references
References 13 publications
4
88
1
1
Order By: Relevance
“…These findings support previously reported findings where MRI measurements of equine carpal cartilage were significantly greater than the histologic measurements. 28 The subjective choice of STIR and PDw sequences as being the best for visualizing cartilage in the current study was supported by the fact that TI=200ms is quite close to STIR imaging at 1.5T (where TI=150ms), which means that the fat signal of the image is close to zero, and cartilage with relatively high water content can be well differentiated from its surroundings. For T2, the image with the shortest TE has the best signal to noise ratio and least T2 weighting, therefore closer to a proton density weighting, which yields a good contrast between cartilage and surrounding tissues.…”
Section: Resultsmentioning
confidence: 63%
See 3 more Smart Citations
“…These findings support previously reported findings where MRI measurements of equine carpal cartilage were significantly greater than the histologic measurements. 28 The subjective choice of STIR and PDw sequences as being the best for visualizing cartilage in the current study was supported by the fact that TI=200ms is quite close to STIR imaging at 1.5T (where TI=150ms), which means that the fat signal of the image is close to zero, and cartilage with relatively high water content can be well differentiated from its surroundings. For T2, the image with the shortest TE has the best signal to noise ratio and least T2 weighting, therefore closer to a proton density weighting, which yields a good contrast between cartilage and surrounding tissues.…”
Section: Resultsmentioning
confidence: 63%
“…A study validating MRI imaging measurements of equine carpal cartilage thickness found a significant correlation between gradient echo and spoiled gradient echo, and spoiled gradient echo and histologic measurements. 28 The same study found that, when calcified cartilage was excluded from the histologic measurement, MRI measurements were significantly greater than histologic measurements. 28 Another previous human study reported good repeatability for cartilage thickness measurements using a 7T scanner, with a coefficient of variation of 1.13%.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…For example, Werpy et al showed that artificially-created osteochondral defects in the fetlock were more accurately represented using high-field systems (1.0 and 1.5T) than with low-field systems (0.27T), with their chosen pulse sequences [2,10]. Even so, the vast majority of publications describing articular cartilage lesions seen on MRI were performed using high-field MRI systems ex vivo on limbs in a research setting [3][4][5][6]. At low field, Olive reported moderate-to-good sensitivity and accuracy when imaging artificially-created, full-and partial-thickness articular cartilage lesions in the coffin joint at 0.27T, by using a combination of sagittal and dorsal T1-weighted GRE sequences (2-3 mm slice thickness) [11].…”
mentioning
confidence: 97%